2022
DOI: 10.3390/sports10120200
|View full text |Cite
|
Sign up to set email alerts
|

Association of Co-Living and Age on the Type of Sports Practiced by Older People

Abstract: Introdution: The environment and the type of co-living of older people are crucial to understanding how the nature of their context influences a healthy lifestyle. However, no studies have investigated to what extent their type of co-living may be associated with the sports and the profile practice according to their age. Objective: This study aimed to assess the association between the types of co-living and the age of the physically active elderly and the sports they practice. Hypothesis: It is thought that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“… 6 Meanwhile, it was also reported that different age groups and living situations of the older adults had distinct types of sports and activities, which might affect their quality of life. 7 It holds significant implications for public health and social welfare. 8 , 9 However, despite improvements in the health of elderly individuals reported in various regions of China, 10 , 11 limited research has focused on the health-related quality of life (HRQoL) of the elderly population in Tibet.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Meanwhile, it was also reported that different age groups and living situations of the older adults had distinct types of sports and activities, which might affect their quality of life. 7 It holds significant implications for public health and social welfare. 8 , 9 However, despite improvements in the health of elderly individuals reported in various regions of China, 10 , 11 limited research has focused on the health-related quality of life (HRQoL) of the elderly population in Tibet.…”
Section: Introductionmentioning
confidence: 99%
“…The engagement in physical activity also yields mental health benefits, for instance, in promoting integration and social interaction with others. Older adults, specifically those aged 70 and above, prefer activities such as dancing, which helps them enjoy increased social engagement with their peers (Parra-Rizo et al , 2022).…”
Section: Introductionmentioning
confidence: 99%